Essays on the sociology of culture - Mannhein, Karl (London Routledge & Kegan Paul Books, 1956)
Karl Mannheim was one of the leading sociologists of the twentieth century. Essays on the Sociology of Culture, originally published in 1956, was one of his most important books. In it he sets out his ideas of intellectuals as producers of culture and explores the possibilities of a democratization of culture.